Sodium bismuth titanate-based lead-free ceramic material, preparation method and application

By doping titanium acid sodium-based ceramic materials to enhance relaxor behavior, the issues of high dielectric loss and low energy density are addressed, resulting in ceramics with improved stability and energy storage capabilities for advanced electronic applications.

CN119661215AActive Publication Date: 2025-03-21XIAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411851104.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Current titanium acid sodium-based ceramic materials face challenges with high dielectric loss, low energy density, and low energy efficiency, particularly in wide temperature ranges, which limits their application in advanced electronic devices requiring stability and reliability.

Method used

The development of titanium acid sodium-based lead-free ceramic materials with compositions such as (1-x)Bi0.5Na0.5Ti03-xSr1/2Nd1/3(Mg1/3Nb2/3)O3 or (1-x)(0.7Bi0.5Na0.5Ti03-0.3SrTiO3)-xNd(Mg2/3Nb1/3)O3, where x ranges from 0.06 to 0.21, involves doping to break long-range order and enhance relaxor behavior, resulting in improved dielectric stability and energy storage properties.

Benefits of technology

The resulting ceramic materials exhibit low dielectric loss, high energy density, and excellent temperature stability, enabling reliable operation in harsh environments, suitable for high-power systems and energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661215A_ABST
    Figure CN119661215A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic material preparation, in particular to a sodium bismuth titanate-based lead-free ceramic material, a preparation method and application, Sr1 / 2Nd1 / 3 (Mg1 / 3Nb2 / 3) O3 doping substitution is performed in (1-x) Bi0. 5Na0. 5Ti03-xSr1 / 2Nd1 / 3 (Mg1 / 3Nb2 / 3) O3, or Nd3 + / (Mg2 / 3Nb1 / 3) 3 + doping substitution is performed in (1-x) (0.7 Bi0. 5Na0. 5Ti03-0.3 SrTiO3), so that the long-range ordered ferroelectricity is destroyed, the relaxation behavior of the ceramic is enhanced, and the dielectric temperature stability of the ceramic material is improved. The sodium bismuth titanate-based lead-free ceramic material with a wide dielectric temperature range and high frequency stability is obtained under the conditions of relatively high dielectric constant and extremely low dielectric loss, and the prepared ceramic material has the characteristics of high breakdown voltage resistance, high energy storage density and excellent dielectric temperature stability, can stably work in severe environments such as high temperature and high electric field, and has wide application prospects. And the method is suitable for a high-pulse power system. The problems that in the prior art, a sodium bismuth titanate-based ceramic material is high in dielectric loss, low in energy storage density, low in energy storage efficiency and narrow in working temperature zone are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic material preparation, specifically to a sodium bismuth titanate-based lead-free ceramic material, a preparation method and an application thereof, and in particular to a high-serving sodium bismuth titanate-based lead-free high-entropy energy storage ceramic material, a preparation method and an application thereof. Background Art

[0002] With the rapid development of human society, energy crisis and environmental pollution are becoming more and more serious. In order to reduce the waste of renewable energy, it is of great significance to develop efficient, reliable, low-cost and environmentally friendly energy storage devices. At present, widely used storage devices include batteries, electrochemical capacitors and dielectric capacitors. As one of the dielectric capacitors, dielectric ceramics have attracted extensive attention and research due to their ultra-long safe service life, excellent anti-fatigue properties and ultra-high power density. Ceramic capacitors prepared with dielectric ceramics are widely used in electronic filters, pulse power devices, renewable energy storage, hybrid vehicles and other fields. With the rapid development of the electronics industry, the application fields of ceramic capacitors are more extensive, and their working environment is becoming more and more complex, which also puts higher requirements on the performance of ceramic capacitors. For example, the operating temperature of electronic equipment in the fields of automotive control systems, manned spaceflight, rocket satellites, oil exploration, etc. needs to be above 150°C. Therefore, this type of electronic equipment not only requires excellent dielectric properties, but also needs to maintain excellent temperature stability in a wide temperature range to improve its reliability in high-temperature applications. For ceramic capacitors used in filters and resonators, the extremely unstable dielectric constant and dielectric loss in high-frequency environments can easily lead to distortion of transmitted signals, which requires ceramic capacitors to have higher frequency stability. However, current dielectric ceramics have problems such as low energy storage density and efficiency, poor temperature stability, and the presence of lead elements that are harmful to health and pollute the environment. They cannot meet the above requirements, limiting their further development and application.

[0003] Bismuth sodium titanate-based ceramics have a high spontaneous polarization intensity (>40μC / cm 2 ) and a relatively high Curie temperature (~320°C) are considered to be a candidate material for capacitors with high energy storage performance. Researchers use the bimodal characteristics of the dielectric temperature spectrum of sodium bismuth titanate-based ceramics to dope components to destroy the long-range order of ferroelectrics and enhance relaxation behavior, thereby obtaining excellent wide temperature stability, which is beneficial to improving the thermal stability of ceramic capacitors and extending their service life. However, due to the sharp increase in dielectric loss of ceramics under high temperature and high frequency, it is difficult to achieve a stable dielectric constant and low dielectric loss in a wide temperature range.

[0004] The Chinese invention with publication number CN117383930A discloses a sodium bismuth titanate-based lead-free energy storage ceramic material with high ferroelectric stability and temperature stability and a preparation method thereof. The general structural formula of the ceramic material is (1-x)(0.85Bi0.5Na0.5TiO3-0.15NaNbO3)-xSrHfO3, where x is 0.04 to 0.15. The ceramic material is prepared by batching, ball milling, pre-sintering, secondary ball milling, screening, tableting and sintering. The preparation method is simple, low in cost, good in repeatability and high in yield. The obtained ceramic material has high ferroelectric stability (cycle stability and frequency stability), good temperature stability and energy storage characteristics. When x is 0.10, the dielectric constant is εr150℃, 100kHz=1065.39 at 100kHz, the dielectric loss tanδ150℃, 100kHz=0.01472, and within the temperature range of 68℃ to 371℃, the capacitance-temperature change rate satisfies TCC150℃≤±15%, the breakdown strength is 250kV / cm, and the maximum polarization strength is 33C / cm 2 , effective energy storage density is 3.05J / cm 3 , the energy storage efficiency can reach 75.9%. The Chinese invention with publication number CN113387697A discloses a sodium bismuth titanate-based ceramic material with high ferroelectric stability, ultra-fast charging and discharging, and high energy storage efficiency, and a preparation method. The general formula of the ceramic material is (1-x)Na0.5Bi0.5TiO3-xCaTiO3, where x represents the molar ratio of CaTiO3 to the total mass, and the value of x is 0.1-0.25. The ceramic material is prepared by batching, pre-sintering, ball milling, tableting, pressureless closed sintering and other process steps. The preparation method of the invention is simple, repeatable and has a high yield. The obtained ceramic material has high ferroelectric stability (frequency stability and cycle stability), extremely low residual polarization intensity, extremely high energy storage efficiency and charging and discharging performance, strong practicality, easy production, and is a lead-free ferroelectric ceramic with excellent performance. It is a new type of alternative material in the field of pulse power material systems. Although both of the above methods greatly improve the energy storage efficiency, the energy storage density is limited and the breakdown resistance is poor due to the reduction of polarization intensity, which still cannot meet the current demand for ceramic capacitors.

[0005] It can be seen that although people have conducted a lot of research on sodium bismuth titanate-based ceramics and have made great progress in sodium bismuth titanate-based relaxation energy storage ceramic capacitors, the design and development of wide temperature range dielectric materials suitable for cutting-edge technology is still extremely lacking. It is necessary to further explore and develop ceramic materials with high serviceability characteristics such as stable high dielectric constant, low dielectric loss and high energy storage density in an ultra-wide temperature range to meet the current development needs of ceramic capacitors. Summary of the invention

[0006] In view of the problems of high dielectric loss, low energy storage density and low energy storage efficiency as well as narrow operating temperature range of sodium bismuth titanate-based ceramic materials in the prior art, the present invention provides a sodium bismuth titanate-based lead-free ceramic material, a preparation method and an application thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a sodium bismuth titanate-based lead-free ceramic material, the general formula of which is: (1-x)Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or (1-x)(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-xNd(Mg 2 / 3Nb 1 / 3 )O3, where x is Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or Nd(Mg 2 / 3 Nb 1 / 3 )The molar ratio of O3 to the total mass of matter is 0.06≤x≤0.21.

[0008] Optionally, the general formula of the ceramic material is: (1-x)Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3, x is Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )The molar ratio of O3 to the total mass of matter is 0.12≤x≤0.21.

[0009] Optionally, the general formula of the ceramic material is: (1-x)(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-xNd(Mg 2 / 3Nb 1 / 3 )O3, x is Nd(Mg 2 / 3 Nb 1 / 3 )The molar ratio of O3 to the total mass is 0.06≤x≤0.12.

[0010] The present invention also provides a method for preparing the sodium bismuth titanate-based lead-free ceramic material as described above, comprising: Mix Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 in a proportion according to a general formula of ceramic materials to obtain a raw material mixture; Pre-calcining and grinding the raw material mixture to obtain pre-calcined powder; The pre-fired powder is ball-milled, sieved, tableted and sintered to obtain sodium bismuth titanate-based lead-free ceramic material.

[0011] Optionally, the method of mixing Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 in a proportion of the general formula of ceramic materials to obtain the raw material mixture is: Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 with a purity of more than 99% are mixed according to the general proportion of ceramic materials, zirconium balls are used as grinding balls, anhydrous ethanol is used as ball milling medium, the mixture is ball milled for 22 to 24 hours, the zirconium balls are separated, and the mixture is dried at 60°C to 80°C to obtain a raw material mixture.

[0012] Optionally, the temperature for pre-firing the raw material mixture is 800° C. to 900° C., and the pre-firing time is 2 to 4 hours.

[0013] Optionally, in the process of ball milling, sieving, tableting and sintering the pre-burned powder, tableting is performed by cold isostatic pressing at a pressure of 180 to 220 MPa, and the tableting time is 5 to 7 minutes.

[0014] Optionally, in the process of ball milling, sieving, tableting and sintering the pre-sintered powder, the sintering is pressureless and closed sintering, the sintering temperature is 1100° C. to 1200° C., and the sintering time is 2 to 4 hours.

[0015] A sodium bismuth titanate-based lead-free ceramic material prepared by the above method, in 10 2 ~10 6 In the Hz frequency range, the dielectric loss of the ceramic material is less than 0.05; at 10kHz and 150℃, the dielectric constant is 720.4-727.3, the dielectric loss is 0.0019-0.0126; the energy storage density is 7.5-10.4J / cm 3 .

[0016] Application of the sodium bismuth titanate-based lead-free ceramic material as mentioned above in the preparation of capacitors.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a sodium bismuth titanate-based lead-free ceramic material, the general formula of which is: (1-x)Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or (1-x)(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-xNd(Mg 2 / 3Nb 1 / 3 )O3, where x is Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or Nd(Mg 2 / 3 Nb 1 / 3 )O3 accounts for the molar ratio of the total mass, 0.06≤x≤0.21. The method is carried out by 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 for Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3Nb 2 / 3 )O3 + Doping substitution, or in (1-x)(0.7Bi 0.5 Na 0.5 Nd Ti03-0.3SrTiO3) 3+ / (Mg 2 / 3 Nb 1 / 3 ) 3+ Doping substitution is to enhance the relaxation behavior of ceramics by destroying the long-range ordered ferroelectricity, thus improving the dielectric temperature stability of ceramic materials. Under the condition of high dielectric constant and extremely low dielectric loss, sodium bismuth titanate-based lead-free ceramic materials with wide dielectric temperature range and high frequency stability are obtained. The prepared ceramic materials have the characteristics of high breakdown voltage, high energy storage density and excellent dielectric temperature stability. They can work stably in harsh environments such as high temperature and high electric field, and are suitable for the application of high pulse power systems.

[0018] Furthermore, at 0.7Bi 0.5 Na 0.5 Nd in Ti03-0.3SrTiO3 system 3+ / (Mg 2 / 3 Nb 1 / 3 ) 3+Doping substitution enriches the types of polar nano-micro-regions with different polarities. The coexistence of rhombic phase and tetragonal phase is beneficial to maintaining high dielectric constant and low dielectric loss, excellent dielectric temperature stability and high energy storage density while broadening the dielectric temperature stability range. It can work in extreme environments and is suitable for the preparation and application of multilayer ceramic capacitors.

[0019] Furthermore, in Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 system, a high entropy component was introduced, using Sr 2+ and Nd 3+ Replace Bi 3+ and Na + , (Mg 1 / 3 Nb 2 / 3 ) 4+ Replace Ti 4+ , a high entropy structure based on sodium bismuth titanate is constructed by multi-element substitution, and the co-doping of multiple elements increases the local structural disorder and charge fluctuation, inducing the generation of a random electric field, and the existence of a random electric field is conducive to enhancing the relaxation behavior and reducing the residual polarization intensity. Therefore, it is beneficial to improve the dielectric stability and energy storage efficiency of ceramics. In addition, the large ion radius Mg 2+ and Nb 5+ The introduction of aggravates the lattice distortion, which is beneficial to grain refinement. The increase in density significantly improves the breakdown voltage of the ceramic. The prepared ceramic material also has the characteristics of high breakdown voltage, high energy storage density, and excellent dielectric temperature stability, and also meets the requirements of extreme working environments.

[0020] The present invention also provides a method for preparing the sodium bismuth titanate-based lead-free ceramic material as mentioned above, wherein the method comprises mixing Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 according to the general proportion of the ceramic material to obtain a raw material mixture; then pre-firing and grinding the raw material mixture to obtain a pre-firing powder; finally, ball milling, sieving, tabletting and sintering the pre-firing powder to obtain the sodium bismuth titanate-based lead-free ceramic material. The preparation method is simple, low in cost, good in repeatability, high in yield and easy to produce. The selected raw materials do not contain lead and are environmentally friendly. The advanced cold isostatic pressing technology is adopted to reduce the risk of cracking and delamination of the green body, and the green body obtained has high density and uniform quality.

[0021] The present invention also provides a sodium bismuth titanate-based lead-free ceramic material prepared by the above method. 2 ~10 6In the Hz frequency range, the dielectric loss of the ceramic material is less than 0.05; at 10kHz and 150℃, the dielectric constant is 720.4-727.3, the dielectric loss is 0.0019-0.0126; the energy storage density is 7.5-10.4J / cm 3 The material has the characteristics of high breakdown voltage, high energy storage density, and excellent dielectric temperature stability, and has broad application prospects in capacitors, energy storage elements, electronic filters, piezoelectric sensors, and other fields.

[0022] For example, the application of the sodium bismuth titanate-based lead-free ceramic material in the preparation of capacitors. The capacitor prepared using the sodium bismuth titanate-based lead-free ceramic material has the characteristics of high energy conversion rate, good temperature resistance, durability and stability, and has broad application prospects in many fields such as electric vehicles, smart grids, aerospace, and communication equipment. In particular, the capacitor can play an important role in occasions requiring high energy density, high efficiency, long life and environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a schematic flow chart of a method for preparing a sodium bismuth titanate-based lead-free ceramic material.

[0024] Figure 2 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic materials prepared in Examples 1-4 of the present invention at room temperature and the changes with frequency.

[0025] Figure 3 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 1 at different test frequencies and temperature.

[0026] Figure 4 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 2 at different test frequencies and temperature.

[0027] Figure 5 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 3 at different test frequencies and temperature.

[0028] Figure 6 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 4 at different test frequencies and temperature.

[0029] Figure 7 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic materials prepared in Examples 1-4 of the present invention and the temperature at 10 kHz.

[0030] Figure 8 The Δε / ε of the ceramic materials prepared in Examples 1-4 of the present invention at 10kHz 150℃ Curves that vary with temperature.

[0031] Fig. 9 The graph shows the change of the unipolar hysteresis loop of the prepared pure BNT-based ceramics under different electric fields.

[0032] Fig.10 This is a diagram showing the change of the unipolar hysteresis loop of the ceramic material prepared in Example 3 of the present invention under different electric fields.

[0033] Fig.11 This is a graph showing changes in energy storage density and energy storage efficiency of the ceramic materials prepared in Examples 1-4 of the present invention.

[0034] Fig.12 It is a comparison chart of the maximum polarization value, residual polarization value and breakdown field strength change of pure BNT ceramics and the ceramic materials prepared in Examples 1-4.

[0035] Fig.13 This is the XRD diagram of the ceramic material prepared in Examples 5-8 of the present invention.

[0036] Fig.14 This is a scanning electron microscope image of the ceramic material prepared in Example 7 of the present invention.

[0037] Fig.15 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic materials prepared in Examples 5-8 of the present invention at room temperature and the changes with frequency.

[0038] Fig.16 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 5 of the present invention at different test frequencies and temperature.

[0039] Fig.17 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 6 of the present invention at different test frequencies and temperature.

[0040] Fig.18 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 7 of the present invention at different test frequencies and temperature.

[0041] Fig.19 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic material prepared in Example 8 of the present invention at different test frequencies and temperature.

[0042] Fig. 20 This is a graph showing the relationship between the dielectric constant and dielectric loss of the ceramic materials prepared in Examples 5-8 of the present invention at 10 kHz and the changes with temperature.

[0043] Fig.21 The Δε / ε of the ceramic materials prepared in Examples 5-8 of the present invention at 10kHz 150℃ Curves that vary with temperature.

[0044] Fig. 22 The temperature change rate of the ceramic material prepared in Examples 5-8 of the present invention satisfies TCC 150℃ ≤ ±15% temperature range curve.

[0045] Fig.23 This is a graph showing the change of the unipolar hysteresis loop of the ceramic material prepared in Examples 5-8 of the present invention under an electric field of 250 kV / cm.

[0046] Fig.24 This is a graph showing changes in energy storage density and energy storage efficiency of the ceramic materials prepared in Examples 5-8 of the present invention. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0048] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0049] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0050] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0051] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0052] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0053] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0054] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0055] The present invention discloses a sodium bismuth titanate-based lead-free ceramic material, the general formula of which is: (1-x)Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or (1-x)(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-xNd(Mg 2 / 3Nb 1 / 3 )O3, where x is Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or Nd(Mg 2 / 3 Nb 1 / 3 )The molar ratio of O3 to the total mass of matter is 0.06≤x≤0.21.

[0056] Furthermore, the general formula of the ceramic material is: (1-x)Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3, x is Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3)The molar ratio of O3 to the total mass of the substance is 0.12≤x≤0.21, preferably, 0.15≤x≤0.21, and further, 0.18≤x≤0.21.

[0057] Furthermore, the general formula of the ceramic material is: (1-x)(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-xNd(Mg 2 / 3 Nb 1 / 3 )O3, x is Nd(Mg 2 / 3 Nb 1 / 3 )The molar ratio of O3 to the total mass is 0.06≤x≤0.12, preferably, 0.08≤x≤0.12, and further preferably, 0.1≤x≤0.12.

[0058] See also Figure 1 The present invention also provides a method for preparing the sodium bismuth titanate-based lead-free ceramic material as described above, comprising: S1: Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 are mixed according to the general proportion of ceramic materials to obtain a raw material mixture, specifically: Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 with a purity of more than 99% are mixed according to the general proportion of ceramic materials, placed in a nylon jar, using zirconium balls as grinding balls and anhydrous ethanol as ball milling media, mixed and ball milled for 22 to 24 hours, the zirconium balls are separated, and dried at 60°C to 80°C to obtain a raw material mixture.

[0059] S2: Pre-calcining and grinding the raw material mixture to obtain pre-calcined powder, specifically: The raw material mixture is placed in an alumina crucible, compacted with an agate rod, covered, pre-fired at 800°C to 900°C for 2 to 4 hours, cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0060] S3: The pre-burned powder is ball-milled, sieved, tableted and sintered to obtain a sodium bismuth titanate-based lead-free ceramic material, specifically: the pre-burned powder is loaded into a nylon jar, fully mixed and ball-milled for 20 to 24 hours, the zirconium balls are separated, and the powder is dried at 60 to 80 degrees Celsius, ground, and passed through a 120 to 180 mesh sieve after grinding. The powder is cold isostatically pressed at a pressure of 180 to 220 MPa, tableted for 5 to 7 minutes, and pressed into a cylindrical body. The cylindrical body is placed on a zirconia plate, and the zirconia plate is placed in an alumina closed sagger, and the powder is sintered at a constant temperature of 1100 to 1200 degrees Celsius for 2 to 4 hours. The powder is naturally cooled to room temperature with the furnace to prepare the sodium bismuth titanate-based lead-free ceramic material.

[0061] The present invention also provides a sodium bismuth titanate-based lead-free ceramic material prepared by the above method. 2 ~10 6 In the Hz frequency range, the dielectric loss of the ceramic material is less than 0.05; at 10kHz and 150℃, the dielectric constant is 720.4-727.3, the dielectric loss is 0.0019-0.0126; the energy storage density is 7.5-10.4J / cm 3 The material has the characteristics of high breakdown voltage, high energy storage density, and excellent dielectric temperature stability, and has broad application prospects in capacitors, energy storage elements, electronic filters, piezoelectric sensors, and other fields.

[0062] For example, the application of the sodium bismuth titanate-based lead-free ceramic material in the preparation of capacitors. The capacitors prepared using the sodium bismuth titanate-based lead-free ceramic material have the characteristics of high energy conversion rate, good temperature resistance, durability and stability, and have broad application prospects in electric vehicles, smart grids, aerospace, communication equipment and other fields, especially in situations requiring high energy density, high efficiency, long life and environmental protection requirements, the capacitors can play an important role.

[0063] Example 1 According to 0.88Bi 0.5 Na 0.5 Ti03-0.12Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 chemically, 9.1444g Bi2O3, 2.0634g Na2CO3, 0.7826g SrCO3, 6.3337g TiO2, 0.9331g Nb2O5, 0.1424g MgO and 0.5944g Nd2O3 with a purity of more than 99.00% were weighed respectively, mixed evenly, put into a nylon jar, used zirconium balls as grinding balls, and anhydrous ethanol as ball milling medium, mixed thoroughly and ball milled for 24 hours, separated the zirconium balls, dried at 80°C for 24 hours, and ground with a mortar to obtain a raw material mixture.

[0064] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0065] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0066] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0067] Example 2 According to 0.85Bi 0.5 Na 0.5 Ti03-0.15Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 chemically, 8.8254g Bi2O3, 1.9914g Na2CO3, 0.9775g SrCO3, 6.1128g TiO2, 1.1729g Nb2O5, 0.1778g MgO and 0.7423g Nd2O3 with a purity of more than 99.00% were weighed respectively, mixed evenly, put into a nylon jar, used zirconium balls as grinding balls, and anhydrous ethanol as ball milling medium, mixed thoroughly and ball milled for 24 hours, separated the zirconium balls, dried at 80°C for 24 hours, and ground with a mortar to obtain a raw material mixture.

[0068] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0069] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0070] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0071] Example 3 According to 0.82Bi 0.5 Na 0.5 Ti03-0.18Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3)O3 chemically, 8.5068g Bi2O3, 1.9195g Na2CO3, 1.1720g SrCO3, 5.8921g TiO2, 1.4031g Nb2O5, 0.2132g MgO and 0.8901g Nd2O3 with a purity of more than 99.00% were weighed respectively, mixed evenly, put into a nylon jar, used zirconium balls as grinding balls, and anhydrous ethanol as ball milling medium, mixed thoroughly and ball milled for 24 hours, separated the zirconium balls, dried at 80°C for 24 hours, and ground with a mortar to obtain a raw material mixture.

[0072] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0073] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0074] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0075] Example 4 According to 0.79Bi 0.5 Na 0.5 Ti03-0.21Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 chemical measurement, respectively weigh out 8.1888g Bi2O3 with purity above 99.00%, 1.8477g Na2CO3, 1.3662g SrCO3, 5.6719g TiO2, 1.6393g Nb2O5, 0.2485g MgO and 1.0376g Nd2O3, mix evenly, put into a nylon jar, use zirconium balls as grinding balls and anhydrous ethanol as ball milling medium, mix thoroughly and ball mill for 24h, separate the zirconium balls, dry at 80℃ for 24h, grind with a mortar to obtain a raw material mixture.

[0076] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0077] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0078] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0079] Example 5 According to 0.94 (0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-0.06Nd(Mg 2 / 3 Nb 1 / 3 )O3 chemically, 6.8059g Bi2O3, 1.5357g Na2CO3, 3.6614g SrCO3, 6.7343g TiO2, 0.2337g Nb2O5, 0.1417g MgO and 0.8874g Nd2O3 with a purity of more than 99.00% were weighed respectively, mixed evenly, put into a nylon jar, used zirconium balls as grinding balls, and anhydrous ethanol as ball milling medium, mixed thoroughly and ball milled for 24 hours, separated the zirconium balls, dried at 80°C for 24 hours, and ground with a mortar to obtain a raw material mixture.

[0080] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0081] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0082] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0083] Example 6 0.92(0.7Bi 0.5 Na 0.5Ti03-0.3SrTiO3)-0.08Nd(Mg 2 / 3 Nb 1 / 3 )O3 chemically, 6.6536g Bi2O3, 1.5013g Na2CO3, 3.5795g SrCO3, 6.5836g TiO2, 0.3112g Nb2O5, 0.1887g MgO and 1.1819g Nd2O3 with a purity of more than 99.00% were weighed respectively, mixed evenly, put into a nylon jar, used zirconium balls as grinding balls, and anhydrous ethanol as ball milling medium, mixed thoroughly and ball milled for 24 hours, separated the zirconium balls, dried at 80°C for 24 hours, and ground with a mortar to obtain a raw material mixture.

[0084] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0085] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0086] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0087] Example 7 According to 0.90(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-0.10Nd(Mg 2 / 3 Nb 1 / 3 )O3 chemically, 6.5018g Bi2O3, 1.4671g Na2CO3, 3.4978g SrCO3, 6.4334g TiO2, 0.3886g Nb2O5, 0.2357g MgO and 1.4757g Nd2O3 with a purity of more than 99.00% were weighed respectively, mixed evenly, put into a nylon jar, used zirconium balls as grinding balls, and anhydrous ethanol as ball milling medium, mixed thoroughly and ball milled for 24 hours, separated the zirconium balls, dried at 80°C for 24 hours, and ground with a mortar to obtain a raw material mixture.

[0088] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0089] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0090] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0091] Example 8 According to 0.88 (0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-0.12Nd(Mg 2 / 3 Nb 1 / 3 )O3 chemically, 6.3502g Bi2O3, 1.4329g Na2CO3, 3.4163g SrCO3, 6.2834g TiO2, 0.4658g Nb2O5, 0.2825g MgO and 1.7689g Nd2O3 with a purity of more than 99.00% were weighed respectively, mixed evenly, put into a nylon jar, used zirconium balls as grinding balls, and anhydrous ethanol as ball milling medium, mixed thoroughly and ball milled for 24 hours, separated the zirconium balls, dried at 80°C for 24 hours, and ground with a mortar to obtain a raw material mixture.

[0092] The raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, heated to 850°C in a muffle furnace at a heating rate of 3°C / min, pre-fired at a constant temperature for 3 h, naturally cooled to room temperature, and ground with a mortar to obtain pre-fired powder.

[0093] The pre-sintered powder was put into a nylon jar, mixed thoroughly and ball-milled for 24 hours, the zirconium balls were separated, dried at 80°C for 24 hours, ground with a mortar, passed through a 120-mesh sieve, and pressed into a cylindrical body with a diameter of 11.5 mm and a thickness of 1 mm in a tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes.

[0094] The cylindrical blank after cold isostatic pressing is placed on a zirconia plate, the zirconia plate is placed in an alumina closed sagger, the temperature is increased to 1130°C at a heating rate of 3°C / min, sintered at a constant temperature for 3 hours, and naturally cooled to room temperature in the furnace to prepare sodium bismuth titanate-based lead-free energy storage ceramic material.

[0095] In order to further test the performance of the sodium bismuth titanate-based lead-free energy storage ceramic material prepared by the present invention, the sodium bismuth titanate-based lead-free energy storage ceramic material prepared in Examples 1-8 was selected respectively, and its surface was polished with 320-mesh sandpaper, and then polished to 0.5 mm thick with 1500-mesh sandpaper and corundum, and then ground into powder after being wiped clean with alcohol ultrasonic, and XRD test was performed using the MiniFlex600 diffractometer produced by Japan Rigaku Co., Ltd. One of the ceramic materials prepared in the above Examples 1-8 was selected for grinding, polishing, ultrasonic, and wiping clean, and silver paste was coated on the upper and lower surfaces of the ceramic sample, respectively, and placed in a muffle furnace at 840°C for 30 minutes, and naturally cooled to room temperature. The dielectric properties of the material were tested using the DMS-2000 high-temperature dielectric impedance spectrometer produced by Bailibo Technology Co., Ltd. One of the ceramic materials prepared in the above Examples 1-8 was selected for grinding, polishing, ultrasonic, and wiping clean with alcohol ultrasonic, and the gold electrode was sputtered, and the ferroelectric tester produced by Radiant, USA, was used for ferroelectric testing.

[0096] See also Figure 2 The relationship between the dielectric constant and dielectric loss of the ceramic materials prepared in Examples 1-4 at room temperature and the frequency is shown. It can be seen that the dielectric constant of the ceramic materials has a platform that is independent of the dielectric frequency, and the frequency stability is excellent. 2 ~10 6 The dielectric loss of ceramic materials in the Hz frequency range is less than 0.04, and as Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 ) With the increase of O3 doping amount, the dielectric constant and dielectric loss decrease, and the frequency stability of ceramic materials gradually improves. Figures 3 to 6 From the relationship diagram of the dielectric constant and dielectric loss of the ceramic materials prepared in Examples 1 to 4 at different test frequencies with temperature, it can be seen that under the test temperature range of -150°C to 450°C, the dielectric constant ε of the ceramic material prepared in Example 4 at 10kHz and 150°C is 150℃,10 kHz =720.4, dielectric loss tanδ 150℃,10 kHz = 0.0019, achieving a large dielectric constant and extremely low dielectric loss. Figure 7 , the relationship between the dielectric constant and dielectric loss of the ceramic materials prepared in Examples 1-4 at 10kHz and temperature, it can be seen that Sr 1 / 2 Nd1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 doping causes a dielectric platform to appear in the dielectric curve in a wide temperature range and gradually widens with the increase of doping amount, indicating that the long-range ordered ferroelectricity of the ceramic is destroyed and the relaxation behavior is gradually enhanced, which is conducive to improving the dielectric temperature stability of the ceramic material. 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 ) As the doping of O3 increases, the dielectric loss gradually decreases. The dielectric loss of the ceramic material prepared in Example 3 is less than 0.02 in an ultra-wide temperature range of 48°C to 404°C. Figure 8 , the Δε / ε of the ceramic materials prepared by Examples 1-4 at 10kHz 150℃ As can be seen from the temperature relationship diagram, it is generally believed that the rate of change of the dielectric constant (Δ ε / ε 150℃ ) does not exceed 15%, indicating that the dielectric constant of the ceramic material has good temperature stability. The results show that as Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 doping broadens the dielectric temperature stability temperature range of ceramic materials. In Example 3, the dielectric temperature change rate TCC of the ceramic material in the temperature range of -17℃~450℃ 150℃ ≤±15%, by Figure 8 It can be seen that the unipolar hysteresis loop of the ceramic material gradually becomes finer and the residual polarization intensity gradually decreases, indicating that the energy storage efficiency of the ceramic material gradually increases. Fig. 9 and Fig.10 It can be seen that pure BNT ceramics are pure Bi 0.5 Na 0.5 The TiO3 ceramic has a large residual polarization value and a low breakdown field strength. Compared with the ceramic material prepared in Example 3, the ceramic material prepared in Example 3 has a higher breakdown voltage, which can reach 480 kV / cm. Fig.11 It can be seen that in the figure, P max is the maximum polarization value, P r is the residual polarization value, E b The effective energy storage density of the prepared pure BNT ceramic is only 1.8 J / cm 3 The energy storage efficiency is only 58.6%, and the breakdown field strength is relatively low, which is 160 kV / cm. However, the ceramic material prepared in Example 3 has excellent energy storage performance, and its effective energy storage density is 7.5 J / cm 3 , the energy storage efficiency is 82.6%. Compared with the prepared pure BNT ceramics, the effective energy storage density is increased by 416%, the energy storage efficiency is increased by 141%, and the breakdown field strength is increased by 300%. Fig.12From the changes in the maximum polarization value, residual polarization value, and breakdown field strength of pure BNT ceramics and the ceramic materials prepared in Examples 1-4, it can be seen that due to the effective reduction of the residual polarization value and the substantial increase in the breakdown field strength, the effective energy storage density and energy storage efficiency of the ceramic material prepared in Example 3 are significantly improved.

[0097] See also Fig.13 From the XRD patterns of the ceramic materials prepared in Examples 5-8, it can be seen that all the prepared ceramics have a perovskite structure and no second phase is observed, indicating that the third component Nd (Mg 2 / 3 Nb 1 / 3 )O3 has completely dissolved into 0.7Bi 0.5 Na 0.5 In the lattice of Ti03-0.3SrTiO3. Fig.14 The surface scanning electron microscope image of the ceramic material prepared in Example 8 of the present invention shows that the average grain size is 0.86 μm, which is similar to the 0.7Bi prepared by Zhang Ying et al. in 2024. 0.5 Na 0.5 Compared with the average grain size of 1.31 μm of Ti03-0.3SrTiO3 ceramics (https: / / doi.org / 10.1016 / j.actamat.2024.120109), the grain size has been significantly refined. Therefore, the ceramic material prepared in Example 7 of the present invention has a dense structure and lower dielectric loss. Fig.15 It can be seen that the dielectric constant of ceramic materials has a platform that is independent of the dielectric frequency, and the frequency stability is excellent. 2 ~10 6 The dielectric loss of ceramic materials in the Hz frequency range is less than 0.05, and as Nd(Mg 2 / 3 Nb 1 / 3 ) With the increase of O3 doping amount, the dielectric constant and dielectric loss decrease, and the frequency stability of ceramic materials gradually improves. Figures 16 to 19 , are the dielectric temperature spectra of the ceramic materials prepared in Examples 5 to 8, respectively. The test temperature range is -150°C to 450°C. Among them, the dielectric constant ε of the ceramic material prepared in Example 8 at 10kHz and 150°C is 150℃,10 kHz =727.3, dielectric loss tanδ 150℃,10 kHz =0.0126, with a larger dielectric constant and lower dielectric loss. Fig. 20 It can be seen that Nd(Mg 2 / 3 Nb 1 / 3 )O3 doping causes a dielectric platform to appear in the dielectric curve within a wide temperature range and gradually widens with the increase of doping amount, indicating that the long-range ordered ferroelectricity of the ceramic is destroyed and the relaxation phase gradually increases, which is conducive to improving the dielectric temperature stability of the ceramic material. Fig.21The Δε / ε of the ceramic materials prepared in Examples 5-8 at 10 kHz 150℃ The temperature-dependent relationship and Fig. 22 The temperature change rate of the ceramic material prepared in Example 5-8 satisfies TCC 150℃ ≤ ±15% of the temperature range, it can be seen that as Nd(Mg 2 / 3 Nb 1 / 3 )O3 doping, the dielectric temperature stable temperature range of the ceramic material gradually widens. The ceramic material prepared in Example 7 has a dielectric temperature change rate TCC in the temperature range of -20℃~407℃. 150℃ ≤ ±15%. Fig.23 The unipolar hysteresis loops of the ceramic materials prepared in Examples 5-8 under an electric field of 250 kV / cm show that as Nd(Mg 2 / 3 Nb 1 / 3 ) With the increase of O3 doping amount, the hysteresis loop of ceramic material gradually becomes finer, indicating that the energy storage efficiency is gradually improved. Fig.24 From the energy storage density and energy storage efficiency of the ceramic materials prepared in Examples 5-8, it can be seen that the energy storage performance of the ceramic material prepared in Example 7 has been significantly improved, and its energy storage density is 10.4 J / cm 3 , the energy storage efficiency is 83.6%.

[0098] Based on the above results, it can be seen that the sodium bismuth titanate-based lead-free energy storage ceramics of the present invention have an ultra-wide dielectric stable temperature range, a high dielectric constant, extremely low dielectric loss, high frequency stability, extremely high breakdown voltage and high energy storage density, and are expected to be used in ceramic energy storage capacitors with high serviceability under high electric fields and high temperatures.

[0099] In summary, the present invention provides a sodium bismuth titanate-based lead-free ceramic material, a preparation method and an application thereof, by 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 for Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 + Doping substitution, or in (1-x)(0.7Bi 0.5 Na 0.5 Nd Ti03-0.3SrTiO3) 3+ / (Mg 2 / 3 Nb 1 / 3 ) 3+Doping substitution destroys the long-range ordered ferroelectricity, enhances the relaxation behavior of ceramics, and improves the dielectric temperature stability of ceramic materials. Under the condition of high dielectric constant and extremely low dielectric loss, sodium bismuth titanate-based lead-free ceramic materials with wide dielectric temperature range and high frequency stability are obtained. The prepared ceramic materials have the characteristics of high breakdown voltage, high energy storage density, and excellent dielectric temperature stability. They can work stably in harsh environments such as high temperature and high electric field, and are suitable for the application of high pulse power systems.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A sodium bismuth titanate-based lead-free ceramic material, characterized in that: The general formula of the ceramic material is: (1-x)Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or (1-x)(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-xNd(Mg 2 / 3Nb 1 / 3 )O3, where x is Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 or Nd(Mg 2 / 3 Nb 1 / 3 )The molar ratio of O3 to the total mass of matter is 0.06≤x≤0.

21.

2. The sodium bismuth titanate-based lead-free ceramic material according to claim 1, characterized in that: The general formula of the ceramic material is: (1-x)Bi 0.5 Na 0.5 Ti03-xSr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )O3, x is Sr 1 / 2 Nd 1 / 3 (Mg 1 / 3 Nb 2 / 3 )The molar ratio of O3 to the total mass of matter is 0.12≤x≤0.

21.

3. The sodium bismuth titanate-based lead-free ceramic material according to claim 1, characterized in that: The general formula of the ceramic material is: (1-x)(0.7Bi 0.5 Na 0.5 Ti03-0.3SrTiO3)-xNd(Mg 2 / 3 Nb 1 / 3 )O3, x is Nd(Mg 2 / 3 Nb 1 / 3 )The molar ratio of O3 to the total mass is 0.06≤x≤0.

12.

4. The method for preparing the sodium bismuth titanate-based lead-free ceramic material according to any one of claims 1 to 3, characterized in that: include: Mix Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 in a proportion according to a general formula of ceramic materials to obtain a raw material mixture; Pre-calcining and grinding the raw material mixture to obtain pre-calcined powder; The pre-fired powder is ball-milled, sieved, tableted and sintered to obtain sodium bismuth titanate-based lead-free ceramic material.

5. The method for preparing sodium bismuth titanate-based lead-free ceramic material according to claim 4, characterized in that: The method of mixing Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 according to the general formula of ceramic materials to obtain the raw material mixture is: Bi2O3, Na2CO3, SrCO3, TiO2, Nd2O3, MgO and Nb2O5 with a purity of more than 99% are mixed according to the general proportion of ceramic materials, zirconium balls are used as grinding balls, anhydrous ethanol is used as ball milling medium, the mixture is ball milled for 22 to 24 hours, the zirconium balls are separated, and the mixture is dried at 60°C to 80°C to obtain a raw material mixture.

6. The method for preparing sodium bismuth titanate-based lead-free ceramic material according to claim 4, characterized in that: The temperature for pre-sintering the raw material mixture is 800° C. to 900° C., and the pre-sintering time is 2 to 4 hours.

7. The method for preparing sodium bismuth titanate-based lead-free ceramic material according to claim 4, characterized in that: In the process of ball milling, sieving, tabletting and sintering the pre-burned powder, the tabletting is performed by cold isostatic pressing at a pressure of 180 to 220 MPa, and the tabletting time is 5 to 7 minutes.

8. The method for preparing sodium bismuth titanate-based lead-free ceramic material according to claim 4, characterized in that: In the process of ball milling, sieving, tabletting and sintering the pre-burnt powder, the sintering is pressureless and closed sintering, the sintering temperature is 1100° C. to 1200° C., and the sintering time is 2 to 4 hours.

9. A sodium bismuth titanate-based lead-free ceramic material prepared by the method according to any one of claims 4 to 8, characterized in that: In 10 2 ~10 6 In the Hz frequency range, the dielectric loss of the ceramic material is less than 0.05; at 10kHz and 150℃, the dielectric constant is 720.4-727.3, the dielectric loss is 0.0019-0.0126; the energy storage density is 7.5-10.4J / cm 3 .

10. Use of the sodium bismuth titanate-based lead-free ceramic material according to any one of claims 1 to 3 in the preparation of capacitors.

Citation Information

Patent Citations

  • Strontium magnesium niobate doped modified sodium bismuth titanate-based energy storage ceramic material and preparation method thereof

    CN111978082A

  • Rare earth modified sodium bismuth titanate-based capacitor energy storage material and preparation method thereof

    CN116768617A

  • Sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material and preparation method thereof

    CN116986900A

  • Bismuth sodium titanate barium titanate strontium titanate calcium titanate based lead-free piezoelectric ceramics

    CN1541979A

  • Ferroelectric ceramic material with a low sintering temperature

    US20070241304A1